Management of FDG avid Benign Sinonasal Schneiderian Papilloma: A Case Report and Review of the Literature. (April 2021) - Shafqat, Iram; Ho, Allen S.; Manzoor, Daniel; Balzer, Bonnie; Wu, Arthur W.
Background: The inverted and oncocytic subtypes of sinonasal Schneiderian papillomas are benign tumors with possible rare malignant transformation and are typically managed with complete surgical resection and close follow-up. While computed tomography (CT) and magnetic resonance imaging (MRI) are mainstays in preoperative evaluation of bony invasion and soft tissue extension of the lesion, their imaging characteristics by 18F-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) is less well characterized. Objective: To describe the clinical presentation and management of a PET positive sinonasal lesion. To conduct a literature review of FDG uptake in benign sinonasal papillomas. Methods: Case report (n = 1) and literature review of similar cases (n = 32). Results: We report the case of a 69-year-old man presenting with an isolated left maxillary sinus mass with avid FDG uptake, discovered on PET/CT imaging. An endoscopic left maxillary mega-antrostomy provided successful definitive treatment for final pathologic diagnosis of oncocytic papilloma. Literature review of cases of sinonasal papillomas with avid FDG uptake found that oncocytic papillomas, on average, exhibit greater uptake than inverted papillomas and both may be mistaken as malignancies on PET. Conclusion: While PET imaging demonstrating avid FDG uptake is associated with an increased risk of malignancy, it does not rule out the possibility of a benign sinonasal papilloma nor other benign inflammatory lesions. Particularly, oncocytic papillomas may have very high FDG uptake and mimic malignant lesions.